Prevalence and associated factors of undernutrition among adult tuberculosis patients in some selected public health facilities of Addis Ababa, Ethiopia: a cross-sectional study. Issue 1 (December 2016) - Dargie, Berihun; Tesfaye, Gezahegn; Worku, Amare
Abstract Back ground The prevalence of undernutrition among adult tuberculosis patients is high in developing countries. However it has not been well explored in Ethiopian situation. Therefore the aim of this study was to determine the prevalence of undernutrition and its associated factors among adult TB patients in some selected public health facilities of Addis Ababa. Methods An institution based cross-sectional study was conducted. The total sample size of the study was 360. The sample size was allocated to the selected health facilities proportional to their size and study subjects were consecutively enrolled to the study during the study period. Data were collected using a pretested structured questionnaire. The data were entered and cleaned by using EPI info version 3.6.1 and transferred to SPSS version 20 for analysis. Bivariate and multivariate logistic regression analyses were done to identify factors that are associated with undernutrition. Results The prevalence of undernutrition was 39.7 % (23.6 % mild, 8.6 % moderate and 7.2 % severe undernutrition). Functional status of the patients (AOR = 2.57; 95 % CI = 1.42, 4.68) and dietary counselling (AOR = 1.79; 95 % CI = 1.03, 3.12) were factors independently associated with undernutrition among adult TB patients. Conclusion The prevalence of undernutrition was found to be very high. Regular nutritional assessment and dietary counselling should be part of the routine care of adult TB patients.